Effects of Ambiguity in Market Experiments - Sarin, Rakesh K.; Weber, Martin (Management Science, 1993)
Prior studies have shown that individuals are averse to ambiguity in probability. Many decisions are, however, made in market settings where an individual's decision is influenced by decisions of others participating in the market. In this paper, we extend the previous research to evaluate the effect of ambiguity on individual decisions and the resulting market price in market settings. We therefore examine an important issue: whether ambiguity effects persist in the face of market incentives and feedback. Two different market organizations, the sealed bid auction and the double oral auction, were employed. The subjects in the experiments were graduate business students and bank executives. Our results show that the individual bids and market prices for lotteries with ambiguous probabilities are consistently lower than the corresponding bids and market prices for equivalent lotteries with well-defined probabilities. The aversion to ambiguity therefore does not vanish in market settings. Our results provide insights into what a manager can expect in bidding situations where the object of the sale (oil leases, mineral rights) involves ambiguity in probability due to, for example, lack of information or prior experience. The results may also be useful in understanding some phenomena in insurance and equity markets.